HEALTHCARE LANGUAGE PROGRAM (HELP) TO ENHANCE STUDENTSâ ENGLISH PROFICIENCY FOR NURSING ACADEMY TOWARD ASEAN COMMUNITY - Nurhidayat, Eka Nurhidayat (Research And Innovation In Language Learning (RILL), 2018)
This research aims to convey the development of English proficiency toward Asean community through Healthcare Language Program (HELP) for Nursing Students. The demand of Asean Community is the use of English, as the language of Asean Community. English become a tool for communicating and connecting with other people around Asean Countries. In the Asean community, there will be more developments in Indonesia. Starting from free trade, foreign companies, and also healthcare sector. Not only the case of trade in goods and services, but also in the traffic of people in the context of labor. As an international language, English is required to interact with the global community, especially in the face of the ASEAN Economic Community. In addition, the role of English is also used in writing article for international journal publication. In other case, English can be very helpful in term of searching source of science about nursing which mostly come from international journal. So, nursing students should be able to master English well. In fact most of them encounter problem with English especially concerning with speaking and writing. Those skills are very important for nusring students to face Asean community. They need some activity and program to enhance English proficiency. This study is an investigation of the English program held by STikes Mahardika Cirebon. This study uses descriptive qualitative method. Meanwhile, the data is collected by using observation, interview, as well as documentation. The descriptive qualitative method covers the English proficiency for nursing students through Healthcare language Program (HELP) toward Asean Community.Â Keywords â English proficiency, Healhcare Language Program, Asean Community